Genomic and functional characterization of a methoprene-tolerant gene in the kissing-bug Rhodnius prolixus - Villalobos Sambucaro, María José (2015)
Metamorphosis, which depends upon a fine balance between two groups of lipid-soluble hormones such as juvenile hormones (JHs) and ecdysteroids, is an important feature in insect evolution. While it is clear that the onset of metamorphosis depends on the decrease of JH levels, the way in which these hormones exert their activities is not fully understood in Triatominae species. The discovery of a Drosophila melanogaster mutant resistant to the treatment with the JH analogue methoprene, led finally to the description of the methoprene-tolerant gene in Tribolium castaneum (TcMet) as a putative JH receptor. Here we present the genomic and functional characterization of an ortholog of the methoprene-tolerant gene in the hemimetabolous insect Rhodnius prolixus (RpMet). The analysis of the R. prolixus gene showed that the exonic structure is different from that described for holometabolous species, although all the critical protein motifs are well conserved. Expression analysis showed the presence of RpMet mRNA in all the tested tissues: ovary, testis, rectum, Malpighian tubules and salivary glands. When juvenile individuals were treated with RpMet specific double strand RNA (dsRNA), we observed abnormal molting events that resulted in individuals with morphological alterations (adultoids). Similarly, treatment of newly emerged fed females with dsRNA resulted in an abnormal development of the ovaries, with eggs revealing anomalies in size and accumulation of yolk, as well as a decrease in the amount of heme-binding protein. Altogether, our results validate that RpMet is involved in the transduction of JH signaling, controlling metamorphosis and reproduction in R. prolixus.